The Influence of Electronic Banking Transactions on Fee Base Income in Conventional Banking Listed on the Indonesia Stock Exchange for the 2018-2021 Period - Gina Anita; Debbie Christine (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
The background of this research is that there is still a research gap between the value of e-banking transactions and the value of fee-based income at several conventional banks listed on the Indonesia Stock Exchange. In addition, this research aims to find out how electronic banking transactions affect fee base income. The factors tested in this study are electronic banking transactions as the independent variable, while fee-based income is the dependent variable. The research method used is descriptive and verification method. The population in this study are conventional banks listed on the Indonesia Stock Exchange for the 2018-2021 period, totaling 41 banks. The sampling technique used is non-probability sampling with purposive sampling method, so that the total sample is 11 companies. The data analysis used is panel data regression analysis using Eviews. The results of the study show that electronic banking transactions and fee-based income in conventional banks listed on the Indonesia Stock Exchange for the 2018-2021 period tend to increase every year. In addition, the results of hypothesis testing show that electronic banking transactions have an effect on fee base income. The magnitude of the effect of electronic banking transactions on fee base income is 75.4%.